Peranan Kebijakan Pendidikan Islam dalam Menghadapi Pandemi Covid-19 - Falih Sunnimadi; Eni Riatul Malikhah; Fery Diantoro (LP2M STIT Palapa Nusantara, 2021)
The Covid-19 pandemic has occurred in our beloved country Indonesia for almost a year. The emergence of the Covid-19 outbreak triggered various changes in various aspects of life, both in terms of social, health, education, and so on. In addition, the Covid-19 outbreak has led to the emergence of various new policies formulated by the government to break the chain of spreading Covid-19. This includes policies in the education sector. In accordance with the policy issued by the Ministry of Education and Culture, that in order to break the chain of the spread of the Covid-19 outbreak, teaching and learning activities at various levels of education are carried out online (online) and offline (outside the network). This is something new in our world of education. Which is usually the teaching and learning process carried out directly. Now, when the Covid-19 pandemic has to be done with the internet media or referred to as online (in the network). With the existence of this policy, it is a challenge for teachers and students as actors of education, especially in areas that lack technology and internet networks.This challenge applies to all teachers of educational institutions, including teachers under Islamic education institutions.